Parenting/internet/kids : domesticating technologies - Green, Fiona J.; Rogers, Jaqueline McLeod (Demeter Press, 2022)
Parenting/Internet/Kids, with three key terms slashed together, conveys the idea that the practice of parenting may extend both to the Internet and to our children - to the extent that both require attention, care and forms of regulation, and, in turn, provide support and enjoyment. While the triadic title is somewhat playful, it also strikes a serious note and introduces layered possibilities: we are not simply raising children who have grown up in the intern.